Practical Deoxygenation of Oxazole N-Oxides by PCl3/Collidine - Shirinian, Valerii Z.; Lonshakov, Ilya A.; Zakharov, Alexey V.; Lvov, Andrey G.; Krayushkin, Mikhail M. (Synthesis, 2019)
A new chemoselective method for the synthesis of 2-aryl-1,3-oxazoles by deoxygenation of the corresponding N-oxides has been developed. As the deoxygenation reagent, a previously unknown complex of collidine with phosphorus trichloride in a 2:1 ratio has been used. The developed method enabled the preparation of a wide range of 2-aryl-1,3-oxazoles comprising various functional groups in good yields. The advantage of this reagent is its tolerance to nitro, methyl, hydroxyl, formyl, and acetyl groups, and double bonds. Due to chemoselectivity and availability of reagents, the method may be used for deoxygenation of N-oxides of other heterocyclic compounds (thiazole, pyridine, quinoline, etc.).
Keywords: deoxygenation; N-oxides; azoles; phosphorus trichloride; collidine; chemoselective; oxazoles